Greek Names in the Territory of the Vascones: Reflection of a Social Group? Onomastics in Graffiti on Roman Pottery from the Region of Navarre (Citerior Hispania) - Ozcáriz Gil, Pablo (Huarte de San Juan. Geografía e Historia, 2024)
The growing collection of graffiti on ceramics in the central and western territory of the Vascones is providing an intriguing onomastic collection, with a high number of cognomina of Greek origin. This article analyses this group, compares it to names of Latin origin and those from lapidary inscriptions, finding significant differences in the social composition of both epigraphic sets. It concludes that graffiti on pottery constitute a historical source in which slaves and freedmen from the Imperial period are represented in a much higher proportion than in lapidary epigraphy.
Keywords: ancient graffiti; Roman onomastics; Vascones; Roman ceramics; Roman slaves and freedmen